Relationships between Auditory Event-Related Potentials and Mood State, Medication, and Comorbid Psychiatric Illness in Patients with Bipolar Disorder - Fridberg, Daniel J. (Bipolar Disord, 2009)
BACKGROUND: Patients with bipolar disorder (BD) exhibit aberrations in auditory event-related potentials (ERPs), although the relationship between these measures and mood state at testing, comorbid psychiatric illness, presence of psychotic features, and medication usage are unclear. The purpose of this study was to investigate the relationships between these factors and auditory ERP measures in BD patients. METHODS: An auditory “oddball” discrimination task was used to elicit ERPs from sixty-nine patients with type I BD and 52 healthy controls. Patients were placed into subgroups based upon their mood state at testing (euthymic or symptomatic), and ANOVA was used to compare amplitude and peak latency measures from the N100, P200, N200, and P300 ERP components across subgroups. Multiple regression was used to investigate relationships between ERP measures and comorbid psychiatric diagnosis, history of psychotic features, and medication status. RESULTS: Relative to healthy control participants, euthymic and symptomatic BD patients exhibited reduced P300 and P200 amplitude, but ERP measures did not differ among BD patients on the basis of mood status. A history of a comorbid anxiety disorder was associated with reduced N200 peak latency, but prolonged P300 peak latency among BD patients. No other relationships between clinical variables and ERP measures were significant. CONCLUSIONS: The results suggest that disrupted auditory attention may be observed in BD patients regardless of their mood state at testing, medication status, or history of psychosis. These results extend previous findings, and provide further evidence for aberrations in the P300 ERP as an endophenotype for BD.